Profiling of phosphorylated metabolites from lung cancer by zeolite loaded Mg–Al–Ce ternary hydroxide (Zeolite@MAC) composite - Rimsha Batool; Batool Fatima; Fahmida Jabeen; Dilshad Hussain; Muhammad Imran; Muhammad Najam-ul-Haq (Heliyon, 2023)
Phosphorylated metabolites are linked to metabolism, and the dysregulation of metabolic reactions brings cancer. Dysregulated levels lead to hyperactivation of glycolytic and mitochondrial oxidative phosphorylation pathways. Abnormal concentrations are the indicators of energy-related disorders. In this work, Zeolite-loaded Mg–Al–Ce hydroxides (Zeolite@MAC) are prepared by co-precipitation and characterized through FTIR, XRD, SEM, BET, AFM, TEM, and DLS. Magnesium–Aluminum–Cerium-Zeolite particles enrich phosphate-containing small molecules. These ternary hydroxides carried out the main adsorption mechanism, which swapped the surface hydroxyl group ligands for phosphate and the inner-sphere complex of CePO4. XH2O. Cerium plays a significant role in the complexation of phosphate, and adding Mg and Al further helps disperse Ce and increase the surface charge on the adsorbent. ΑTP and AMP are the standard molecules for parameter optimization. Zeolite@MAC enriches phosphorylated metabolites followed by their desorption via UV–vis spectrophotometry. MS profiles for healthy and lung cancer serum samples are obtained for phosphorylated metabolites. Characteristic phosphorylated metabolites have been detected in lung cancer samples with high expression. The role of phosphorylated metabolites is explored for abnormal metabolic pathways in lung cancer. The fabricated material is sensitive, selective, and highly enriched for identifying phosphate-specific biomarkers.